Development and validation an HPLC-UV method for determination of esomeprazole and pirfenidone simultaneously in rat plasma: Application to a drug monitoring study - Dural, Emrah; Köz, Sema Tülay; Köz, Süleyman (Istanbul University, 2021)
Background and Aims: It has been observed that the combined treatment of esomeprazole and pirfenidone provides increased efficacy in the treatment of pulmonary fibrosis disease, recently. The aim of this study is to develop a simple, sensitive, and reliable high-performance liquid chromatography method to be used in drug monitoring to increase the effectiveness of esomeprazole and pirfenidone in treatment and to reduce their adverse effects. Methods: Separation was conducted with a C18 reverse-phase column (4.6 mm x 250 mm, 5 mu m) used as a mobile phase prepared with the phosphate buffer (10 mM KH2PO4 and 10 mM K2HPO4) and acetonitrile (60:40, v/v) by an isocratic flow (1 mL/min). Mobile phase pH was adjusted to 3.0. Ultraviolet detection was accomplished at 305 nm. The column oven was held at 35 degrees C to ensure an efficient analytical separation. Results: Analytical recovery of esomeprazole was between 92.43 and 105.36% and for pirfenidone it was found between 89.56 and 104.32%. Accuracy values of esomeprazole and pirfenidone were determined between (-2.90) - 4.22 and (-4.45) - 5.78, respectively. Precision (RSD%) was <= 7.89. The quantification limit was determined as 0.58 and 0.36 ng/mL. Plasma esomeprazole and pirfenidone levels were found as 0.87-8296.87 ng/mL (612.99 +/- 2212.20, mean +/- standard deviation) and 0.45-238.60 ng/mL (61.44 +/- 76.35, mean +/- standard deviation), respectively. Conclusion: Unexpectedly high RSD values were observed in both plasma (360.88%) and dose-rated results (89.61%) of esomeprazole, and pirfenidone were thought to be related to individual metabolism differences.
Keywords: Esomeprazole; Pirfenidone; Rat Plasma; Method Validation; HPLC-UV